The Möbius Paradigm: A transformative approach for integrating stakeholder perspectives when navigating dilemmas in complex operating environments - Linda O’Riordan; Charles Hampden-Turner (International Journal of Corporate Social Responsibility)
Abstract Amidst the growing complexity and uncertainty of today’s operating environments, traditional binary thinking—reducing choices to limited “either/or” decisions—often falls short. To address these nuanced challenges and the conflicting opportunities and threats shaped by diverse stakeholder perspectives, a radically more sophisticated approach is needed. This paper introduces The Möbius Paradigm, a transformative approach which transcends outdated paradigms through systems thinking. By embracing Möbius infinity loop pathways, leaders inspired by radical empathy can transcend simplistic dichotomies, adopting a more holistic and sustainable framework for resolving complex dilemmas. The study highlights the critical challenges faced by choice-makers navigating diverse perspectives within complicated environments, emphasising dynamic stakeholder relationship management as essential for successful leadership. It offers practical examples of how Möbius Mindsets, Logic, and Thinking can be applied to multifaceted scenarios, fostering inclusive, adaptive, and conscious solutions. By integrating awareness of underlying values in choice-making, the Möbius Paradigm enables profound change, bridging the major divides of our time. This approach promotes the realisation of sustainable outcomes, enhancing well-being in business and beyond.